Characterization of the physicochemical properties and extraction optimization of natural melanin from Inonotus hispidus mushroom. (30th March 2019) - Hou, Ruolin; Liu, Xin; Xiang, Kaikai; Chen, Liangtao; Wu, Xiaoping; Lin, Wenxiong; Zheng, Mingfeng; Fu, Junsheng
Highlights: IH melanin was isolated and analyzed for the first time. IH melanin was produced by solid fermentation. IH melanin was characterized by SEM, DLS, UV, IR, EPR and elemental analysis. The ultrasonic-assisted extraction process parameters of IH melanin were determined. IH melanin had a good stability. Abstract: In this study, solid-state fermentation was used to produce Inonotus hispidus melanin (IH melanin). Its physicochemical properties were characterized, and ultrasonic-assisted extraction was used to optimize its extraction process. Characterization techniques like elemental analysis and so on were used to identify melanin. The solubility, stability, and antioxidant activity were also measured. Furthermore, the extraction process of IH melanin was optimized. The results showed that the pigment could be defined as dihydroxy phenylalanine (DOPA)-melanin, it displayed irregular spherical and ellipsoidal structures with average size of 89.33 nm. Melanin has a specific stability and shows antioxidant activity. The optimal extraction parameters of melanin were a NaOH concentration of 0.56 mol/L, solid-liquid ratio of 1:50, ultrasonic power of 300 W, extraction temperature of 70 °C, and ultrasonic time of 70 min. This study was the first time that IH melanin was obtained. The results may be applied to health food or food additives.